Organisational resilience concepts, integration and practice - Bhamra, Ran, 1965- (CRC Press, 2016)
The book captures the diversity and depth of current thinking about research on organizational-related resilience. The book explains fundamental concepts and clarifies some underlying ideas from diverse fields of resilience-related research. It examines how some of these concepts and ideas have been integrated into specific research activity and used to further develop their respective fields of enquiry.